The specifics of applying systemic psychotherapy to team sports games - Piepiora, P. A.; Petre, L. M.; Vveinhardt, J. (Frontiers in Psychology, 2025)
High-level team sports competition creates considerable degree of mental workload for the players, particularly in teams with prominent players displaying characteristics of subclinical narcissism. This affects team effectiveness, which is contingent upon the harmonization of the players` personalities. This perspective examines the specific application of systemic psychotherapy in team sports games. We analyze key factors including team compositions, therapeutic processes, and the factors that contribute to the onset and persistence of pathological symptoms. Our analysis reveals that while systemic psychotherapy effectively addresses team dynamics by treating the team as a unified system, its success depends on multiple variables that influence treatment outcomes. Understanding these specifics enables more effective implementation of systemic psychotherapy in a team sports, though its effectiveness is not constrained by universal patterns. This perspective contributes to expanding the therapeutic approaches in competitive team sports.